2016
DOI: 10.1021/acs.chemmater.6b01897
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Crosslinked and Physically Stable Polymer Coatings with Chemically Labile and Dynamic Surface Features Fabricated by Treatment of Azlactone-Containing Multilayers with Alcohol-, Thiol-, and Hydrazine-Based Nucleophiles

Abstract: We report approaches to the design of covalently crosslinked and physically stable surface coatings with chemically labile and dynamic surface features based on the functionalization of azlactone-containing materials with alcohol-, thiol-, and hydrazine-based nucleophiles. Past studies demonstrate that residual azlactone groups in polymer multilayers fabricated by the reactive layer-by-layer assembly of poly(2-vinyl-4,4-dimethylazlactone) and branched poly(ethylenimine) can react with amine-based nucleophiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…Past studies from our group have demonstrated that interfacial reactions between amine-reactive poly­(2-vinyl-4,4-dimethylazlactone) (PVDMA) and the amine-containing polymer poly­(ethylenimine) (PEI) can drive LbL assembly into films that are either thin, smooth, and relatively featureless at the nanometer scale, or thicker (micrometer-scale) with significant nano- and microscale surface features and substantial nanoscale porosity. These PEI/PVDMA multilayers are potentially useful in at least three ways: (i) similar to other LbL processes, these materials can be fabricated on a broad range of topologically complex substrates, (ii) the assemblies that result exhibit superior stabilities in complex chemical environments owing to the presence of hydrolytically stable amide-based cross-links, and (iii) the resulting films contain residual azlactone groups that can be used to further functionalize and tailor bulk and surface properties by reactions with a range of nucleophiles . These useful properties make PEI/PVDMA multilayers a versatile platform for the elaboration of a broad range of new functional materials, including tailored biointerfaces, , reactive polymer-based capsules, and new types of chemical and biomolecular sensors .…”
Section: Introductionmentioning
confidence: 99%
“…Past studies from our group have demonstrated that interfacial reactions between amine-reactive poly­(2-vinyl-4,4-dimethylazlactone) (PVDMA) and the amine-containing polymer poly­(ethylenimine) (PEI) can drive LbL assembly into films that are either thin, smooth, and relatively featureless at the nanometer scale, or thicker (micrometer-scale) with significant nano- and microscale surface features and substantial nanoscale porosity. These PEI/PVDMA multilayers are potentially useful in at least three ways: (i) similar to other LbL processes, these materials can be fabricated on a broad range of topologically complex substrates, (ii) the assemblies that result exhibit superior stabilities in complex chemical environments owing to the presence of hydrolytically stable amide-based cross-links, and (iii) the resulting films contain residual azlactone groups that can be used to further functionalize and tailor bulk and surface properties by reactions with a range of nucleophiles . These useful properties make PEI/PVDMA multilayers a versatile platform for the elaboration of a broad range of new functional materials, including tailored biointerfaces, , reactive polymer-based capsules, and new types of chemical and biomolecular sensors .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] For a reactive group to be suited for postpolymerization modification, it must (i) be compatible with polymerization conditions (or come with an easily removable protecting group) and (ii) allow for selective and efficient chemical modification, ideally under mild conditions. Commonly used chemical groups include the nucleophile-reactive epoxide, 6,7 azlactone, [8][9][10][11] and activated esters 12 as well as unsaturated groups such as dienes and alkynes which can undergo cycloadditions and reactions with thiols. 13,14 A functional group that remains underexplored in the polymer chemistry arena is the pentafluorobenzene (PFB) motif, which undergoes selective nucleophilic aromatic substitution reactions of the para-fluoride (which is the most activated having two ortho and two meta fluoride neighbors).…”
Section: Introductionmentioning
confidence: 99%
“…As a step toward the design of new azlactone-functionalized multilayers that degrade in aqueous environments, we recently reported a backbone degradable azlactone-functionalized copolymer that can be used as a building block for covalent assembly (in this case, reactive assembly leads to the formation of hydrolytically stable amide/amide-type bonds, and subsequent polymer backbone hydrolysis promotes film degradation and disassembly. 20 As an alternative approach, we also recently reported the fabrication of degradable multilayers by the reactive layer-by-layer assembly of non-degradable PVDMA and chemically or enzymatically degradable polyamine building blocks (this approach leads to reactive films that degrade gradually either by chemical hydrolysis or upon the addition of enzymes that can degrade the polyamine components of the films). 21 These approaches are straightforward to implement, and lead to polymer/polymer-based multilayers with new functional properties well suited for applications in biological, biomedical, biotechnological, or environmental contexts.…”
Section: Introductionmentioning
confidence: 99%